The blood indices of the Baltic salmon fry reared in Latvian fish hatcheries during various physiological periods - Glagoleva, T.P. (Baltijskij Nauchno-issledovatelskij Institut Rybnogo Khozyajstva; "Zvaigzne", 1970)
The investigation was carried out in the fish hatchery "Karli" from 1966 to the autumn 1968. The blood composition of salmon (Salmo salar) fry was studied in the wintering period and during their transition to the smolt stage. The morphological composition of blood was analyzed in the fry retained in the hatchery for the second winter, and in the group of fry which attained the smolt stage by June. The results of the observations for both years fully coincided. It was established that the characteristic changes in blood up to the silvering could be applied, in combination with other physiological and biochemical indices, for specification of the time and place of release of the fry from the Latvian hatcheries. Published Not Known